Ecological models and dynamics (New York : Garland Science/Taylor & Francis, 2006)
Ecological models and dynamics uses mathematical models and computer simulations to study the dynamics of ecosystems, both natural and in response to disturbances
Title from title screen
Minimum system requirements (Windows): Any compatible computer with Pentium or equivalent CPU; Microsoft Windows XP/Vista; color monitor capable of displaying at least 16-bit ('thousands' of colors) at 1024 x 768; DVD-ROM or CD-ROM Drive; at least 500 Mb of Physical RAM; software requirements: Microsoft's PowerPoint (version 2002 or later, required for the PowerPoint version only),Microsoft Excel, Adobe Reader (version 9.0 or later), and PTC Mathcad (version 12 or later). PDF copies of Mathcad files are provided in case the Mathcad application is not available. A LabVIEW run-time engine is required for access to the LabVIEW executables. An installer for that engine is included on the CD
Minimum system requirements (Macintosh): Macintosh 1 GHz or faster G3, G4, or Intel processor running OS X or later; color monitor capable of displaying at least 16-bit ('thousands' of colors) at 1024 x 768; DVD-ROM or CD-ROM drive; at least 500 Mb of Physical RAM; Software requirements: Microsoft PowerPoint (from Office 2004 or later, required for the PowerPoint version only - not recommended), Microsoft Excel, Adobe Reader (version 9.0 or later). The LabVIEW run-time engine cannot be installed on Mac OS X, and software to run the Mathcad files is not available for that operating system
Keywords: Biotic communities -- Mathematical models; Biotic communities -- Computer simulation; Ecology -- Simulation methods